High road or common neoliberal trajectory? Collective bargaining, wage share, and varieties of capitalism - Mpuku, Mutale Natasha Muchule (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
Wage shares have been falling since the 1980s across developing and developed countries. There has also been a downward trend with labour market institutions in these countries, with a few exceptions. This thesis analyzes these trends using firstly an extended literature review and secondly an econometrics analysis of a panel of 36 countries over 39 years. The extended literature review identified two broad competing narratives surrounding this topic: the mainstream and the alternative growth narratives. They both focus on two different growth regimes, the former, posits that growth is profit-led and the latter that growth is wage-led. Both are not 'zero sum' processes and seem to offer the same end result (growth and development). However, profit-led growth seems to have two problems. First, at least in the medium run, there is a trade-off between growth and income distribution. And secondly, profit-led growth is contradictory at the global level. Wage-led growth, which offers a 'high road' approach, seems far more appealing. Furthermore, several authors, including in South Africa, have claimed that regime-switching (to wage-led growth), is possible, and it seems that labour market institutions may play an important role in facilitating such a switch. However, the empirical literature, especially regarding middle- and low-income countries, is sparse and inconclusive. The panel data analysis provided by this thesis was not conclusive in establishing whether the wage-led, high road path is still viable for countries like South Africa. However, it did not find strong evidence of the contrary. The thesis concluded that there is scope for further research in this field and makes certain suggestions in this regard.
Keywords: Collective bargaining; Globalization; Labor union members; Wages -- Statistics; Income distribution; Economic development; Neoliberalism; Capitalism